Kualitas Sensori Keripik Tape Singkong Kuning dengan Perbedaan Proporsi Tape dan Tapioka - Ananda Dwi Millenia; Lilis Sulandari; Ita Fatkhur Romadhoni; Andika Kuncoro Widagdo (Pusat Riset dan Inovasi Nasional, 2025)
Casavva tape chips made from fermented yellow cassava (tape) and tapioca flour with a focus on the proportion of tape (fermented cassava) and tapioca flour. This study used single anova and duncan test to analyze the differences in sensory characteristics between three different proportions of yellow cassava tape and tapioca. The findings revealed that the combination of 75% fermented yellow cassava(tape) and 25% tapioca flour produced the most preferred shape, characterized by a uniform and attractive appearance, with an average score of 2.80, indicating a round shape with relatively neat edges. In contrast, a higher proportion of tape (85%) produced a softer and less stable dough, which led to a less desirable round shape. In addition, color analysis showed that the same proportion (75% tape and 25% tapioca) also produced the brightest and most attractive color, with an average score of 2.89. These results indicate that adjusting the ratio of tapioca flour can significantly improve the sensory quality of cassava tape chips, making them more attractive to consumers. The study concluded that the inclusion of tapioca flour improved dough stability, resulting in better shaped and colored chips, which could benefit manufacturers aiming to improve product quality.